Effects of 24 Weeks of Growth Hormone Treatment on Bone Microstructure and Volumetric Bone Density in Patients with Childhood-Onset Adult GH Deficiency. (13th March 2020) - Yang, Hongbo; Yan, Kemin; Xu, Yuping; Wang, Linjie; Zhang, Qi; Gong, Fengying; Zhu, Huijuan; Xia, Weibo; Pan, Hui
Abstract : Objective . Adults with childhood-onset growth hormone deficiency (CO AGHD) have prominently impaired volumetric bone density (vBMD) and bone microarchitecture. Effects of recombinant human growth hormone (rhGH) on bone microarchitecture in CO AGHD were insufficiently evaluated. The objective of this study is to assess the effects of rhGH on bone microarchitecture and vBMD in CO AGHD patients. Design . In this single-center prospective study, nine CO AGHD patients received rhGH treatment for 24 weeks. High-resolution peripheral quantitative computerized tomography (HR-pQCT) of distal tibia and radius was performed at baseline and at the end of treatment. Main outcomes were vBMD and morphometric parameters from HR-pQCT. Results . After 24-week treatment, IGF-1 SDS gradually increased from −3.31 ± 1.56 to −1.92 ± 1.65 (p = 0.113 ). Serum phosphate (1.17 ± 0.17 vs. 1.35 ± 0.18 mmol/L, p = 0.030 ), alkaline phosphatase (83.6 ± 38.6 vs. 120.5 ± 63.7, p = 0.045 ), and β -CTX (0.67 ± 0.32 vs. 1.09 ± 0.58, p = 0.022 ) were significantly elevated. In distal tibia, total vBMD (200.2 ± 41.7 vs 210.3 ± 40.9 mg HA/cm 3, p = 0.017 ), cortical area (89.9 ± 17.7 vs 95.5 ± 19.9 mm 2, p = 0.032 ), and cortical thickness (0.891 ± 0.197 vs 0.944 ± 0.239 mm, p = 0.028 ) were significantly improved. Trabecular area decreased from 795.3 ± 280.9 to 789.6 ± 211.4 mm 2 (p = 0.029 ). Trabecular bone volume fraction increased from 0.193 ± 0.038 to 0.198 ± 0.036 (p = 0.027 ). In radius, cortical perimeter (74.1 ± 10.0 vs 75.0 ± 10.9 mm, p = 0.034 ), trabecular thickness (0.208 ± 0.013 vs 0.212 ± 0.013 mm, p = 0.008 ), trabecular separation (0.743 ± 0.175 vs 0.796 ± 0.199 mm, p = 0.019 ), and inhomogeneity of network (Tb.1/N.SD) (0.292 ± 0.087 vs 0.317 ± 0.096 mm, p = 0.026 ) were significantly improved, while trabecular number (1.363 ± 0.294 vs 1.291 ± 0.325 1/mm, p = 0.025 ) decreased significantly. Conclusions . Our results provide evidence for improvement of vBMD and bone microarchitecture in AGHD patients at a relatively early stage of rhGH treatment.